Efeitos dos reguladores do crescimento e da pressão reduzida no amadurecimento do tomate (Lycopersicon esculentum Mill) - Awad, Marcel; Lamano, T L C; Stradiotto, F R (Revista Ceres, 2025)
Mature green tomato fruits were treated by immersion (2 min.) in solutions of ethephon, IAA, NAA and 2,4,5-TP (100 ppm), were given 750 ug of ethephon at the stem scar or wore placed in low pressure atmospheres (250 mm Hg). The ethephon treated fruits showed a faster red color development than control, IAA, NAA and 2,4,5-TP treated fruits. This difference was reduced as maturity progressed. Fruits placed in low pressure atmospheres showed a considerable delay in their ma- turity (40 days) without achieving the full red color typical of the variety.